Investigation of self-assembly properties and the effect of tween series co-surfactants on the stability of nonionic branched-chain glycolipid hexosomes - Sazalee, S.A.; Ahmad, Noraini; Hashim, Rauzah (Elsevier, 2017)
Sugar-based surfactants have recently drawn much attention due to their nonionic and bio-friendly properties. These glycolipids are also popular because they can be found in nature or synthesized (e.g. alkyl polyglucosides) from cheap natural resources. In this research, the liquid crystalline and self-assembly properties of a novel branch alkylated glycolipid, namely 2-hexyldecyl-β(/α)-D-glucoside (αβ-Glu-OC10C6), were studied using differential scanning calorimetry (DSC), optical polarizing microscopy (OPM) and small-angle X-ray scattering (SAXS). The αβ-Glu-OC10C6 in anhydrous condition formed a columnar phase with focal conic texture, whereas in the binary aqueous system, αβ-Glu-OC10C6 formed inverse hexagonal dispersions known as hexosomes. The critical aggregation concentrations (CACs) were studied for the branched-chain glycolipid when this was mixed with nonionic co-surfactants (Tween series). The addition of co-surfactants to the glycolipid dispersions reduced the CAC value of αβ-Glu-OC10C6, thus making the system more stable. The formation of mixed surfactant hexosomes was further investigated in terms of their particle size and morphology by using a particle sizer and a transmission electron microscope (TEM), respectively. Furthermore, the particle size variations and particle migration were investigated using light backscattering measurements for 24 h. In the previous study, αβ-Glu-OC10C6 hexosomes produced were unstable because the balance between hydrophilic and lipophilic was not optimum to stabilize the formation of a stable double layer. Therefore, the addition of co-surfactant Tween series reduced the particle size and enhanced the stability of αβ-Glu-OC10C6. Thus, branched-chain glycolipid provided an alternative nonionic surfactant with interesting phase behaviour as a drug carrier system for various applications.